Algebra

posted by .

x^1/2 * y^1/6 *z^1/5. We are to use rational exponents to write an expression.



The sqrt of x - the sqrt of y, over the sqrt of x + the sqrt of y. I need to simplify and use radicals as needed. I obviously do but what...?? Please assist.

Thank you.

  • Algebra -

    I'm not quite sure I understand the second question, but I'll take a guess. You want to simplify

    {sqrt(x) - sqrt(y)} / {sqrt(x) + sqrt(y)}.

    Multiply the top and bottom of this expression by {sqrt(x) - sqrt(y)}. The numerator will then be {x - 2.sqrt(xy) + y}, and the denominator will be (x - y). You've now only got square roots in the numerator. Is that what you need?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math calculus please help!

    l = lim as x approaches 0 of x/(the square root of (1+x) - the square root of (1-x) decide whether: l=-1 or l=0 or l=1 Let me make sure I understand the question. Do we have lim x->0 x/[sqrt(1+x) - sqrt(1-x)] ?
  2. Inequality

    When I solve the inquality 2x^2 - 6 < 0, I get x < + or - sqrt(3) So how do I write the solution?
  3. Math(Roots)

    sqrt(24) *I don't really get this stuff.Can somebody please help me?
  4. math,algebra,help

    Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces …
  5. Math

    How do you find a square root of a number that's not a perfect square?
  6. Mathematics

    sqrt 6 * sqrt 8 also sqrt 7 * sqrt 5 6.92820323 and 5.916079783 So you can see the steps — sqrt 6 * sqrt 8 = sqrt 48 sqrt 7 * sqrt 5 = sqrt 35 I hope this helps a little more. Thanks for asking.
  7. Math Help please!!

    Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
  8. Calculus

    Please look at my work below: Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2 …
  9. Algebra

    Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work. sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2) x*sqrt 7x-49*x ^^^ would this be my final answer?
  10. algebra

    am I right? 1. Simplify radical expression sqrt 50 5 sqrt ^2*** 2 sqrt ^5 5 sqrt ^10 5 2. Simplify the radical expression sqrt 56x^2 28x 2x sqrt 14*** 2x sqrt 7 sqrt 14x2 3. Simplify the radical expression. sqrt 490y^5w^6 2 sqrt 135y^2

More Similar Questions